Climate Models Indicate Compensating Effects between Anthropogenic Greenhouse Gases and Aerosols on the 2022 Central Andes Spring Drought - Kam, Jonghun (2024)
CMIP6 simulations showed a weak human contribution to 2022-like Central Andes spring droughts, due to compensating impacts between anthropogenic greenhouse gases and aerosols.